The Influence of Water Mass Mixing and Particle Dissolution on the Silicon Cycle in the Central Arctic Ocean - Liguori, Bianca T. P.; Ehlert, Claudia; Pahnke, Katharina (Frontiers in Marine Science, 2020)
The use of the silicon isotope composition of dissolved silicon (δ30Si-DSi) to understand the marine silicon cycle has been increasing in recent years. Here we present δ30Si-DSi and δ30Si of biogenic silica (δ30Si-bSiO2) in the intermediate to deep waters of the Central Arctic Ocean (AO) aiming at investigating in more detail the relative influence of water mass mixing and particle flux on the Si cycle in the AO. Comparing the δ30Si-DSi with the water mass composition derived from Optimum Multiparameter analysis, we were able to test the influence of the water masses in the δ30Si-DSi distribution. We were able to show the dominant Atlantic Water (AW) influence at the stations close to the Fram Strait (station 32 and 40, δ30Si-DSi = 1.51 ± 0.11‰, 2SEM, n=3) and the only small δ30Si-DSi modification when compared to the endmember value from a previous study (δ30Si-DSi = 1.55‰). The Dense Arctic Atlantic Water, dominating from 200 to 500 m water depth (except for stations 32 and 40, where it was present only at 500 m), was marked by heavier δ30Si-DSi of 1.62 ± 0.06‰ (2SEM, n=21). This is probably due to the influence of entraining equally dense water from the shelves. Due to productivity and Si utilization on the shelves, both water and bSiO2, that were transported laterally into the Central AO, were characterized by higher δ30Si, with δ30Si-bSiO2 of 1.64 ± 0.13‰ (2SEM, n=7). Particle dissolution at greater depths did not play a major role in the δ30Si-DSi of deep waters due to the low bSiO2 concentrations at these greater depths. Outflowing water masses from the AO present different δ30Si-DSi, with lower values around 1.46‰ originating from the Central AO influencing predominantly DSOW and ISOW, and higher values around 2‰ originating from the Canadian AO influencing predominantly LSW. Those signatures correspond with the δ30Si-DSi found in the North Atlantic. Consequently, the AO potentially presents several isotopically different endmembers that contribute to the deep water formed in the North Atlantic.